Identification of high mortality risk patients and prediction of outcomes in delirium by Bispectral EEG - Shinozaki, Gen (J Clin Psychiatry, 2019)
BACKGROUND: Delirium is common and dangerous, yet under-detected and under-treated. Current screening questionnaires are subjective and ineffectively implemented in busy hospital workflows. Electroencephalography (EEG) can objectively detect the diffuse slowing characteristic of delirium, but it is not suitable for high-throughput screening due to size, cost, and the expertise required for lead placement and interpretation. We hypothesized that we could develop an efficient and reliable point-of-care EEG device for high-throughput screening. METHODS: This is a prospective study to measure bispectral EEG (BSEEG) from the elderly inpatients to assess their outcomes conducted at the University of Iowa Hospitals and Clinics (UIHC) from January 2016 to October 2017. A BSEEG score was defined based on the distribution of 2938 EEG recordings from the 428 subjects, who were assessed for delirium; primary outcomes measured were hospital length of stay (LOS), discharge disposition, and mortality. RESULTS: 274 patients had BSEEG scores data available for analysis. Delirium and BSEEG score had a significant association (P<0.001). Higher BSEEG scores were significantly correlated with LOS (P<0.001) as well as with discharge not to home (P<0.01). Hazard ratio for survival controlling for age, gender, Charlson Comorbidity Index and delirium status was 1.35 (95% confidence interval = 1.04 to 1.76, P=0.025). CONCLUSION: We have developed an efficient and reliable device that provides an objective measurement of delirium status. This BSEEG score is significantly associated with pertinent clinical outcomes of mortality, hospital length of stay, and discharge disposition. The BSEEG score better predicts mortality than clinical delirium status. We identified a previously unrecognized sub-population of patients without clinical features of delirium who are at increased mortality risk.